The Students' Perception Of The Online English Writing Learning Process - Marwito Wihadi; Vina Agustiana; Tika Kurniawati (Borneo Educational Journal (Borju), 2023)
Abstract: This study pinpointed on how students perceived online learning process, particularly on writing narrative learning. It employed the quantitative research approach by undertaking a survey as the research instrument. Through the use of a closed-ended questionnaire, the data were gathered from one hundred eighty seven (187) students in the eleventh and twelfth grades in one of Senior High School in Kuningan, West Java. It was discovered that English writing online learning had a variety of responses in three categories. Based on the analysis of the data, it was revealed that students' perceptions of the process of learning English writing online were positive in the participation category (70.5%), neutral in the accessibility category (44.7%), and positive in the material and assignment delivery category (60.2%). It is concluded that respondents struggling with English writing narrative online learning feasibly overcome these difficulties by rereading the summary, thus becoming more independent, and taking greater responsibility for each of their duties.